Child and adolescent psychiatry perspective in forensic cases - (:unkn) unknown (Nova Science Publishers, Inc., 2021)
Forensic assessment of children and adolescents is an important and specialized area in child and adolescent psychiatry. Nearly every child and adolescent psychiatrist or other professional working with children and adolescents is requested to assess forensic cases and is expected to write objective forensic reports with clear language. A multidisciplinary approach helps to reach a more integrative perspective and to identify blurry points in the cases, thereby contributing to the quality of the evaluation. Child maltreatment may affect all domains of development and may have short and long term adverse effects on mental and physical health. Maltreatment can also negatively affect the development of a secure attachment between the child and his/her primary caregivers, and may jeopardize the ability to build healthy relationships throughout life. Therefore, recognizing abuse and neglect, reducing the risk, increasing resilience, and helping to reach the best possible outcome for the child/adolescent are important in terms of the approach to maltreatment. Therefore I would like to describe the key points related to the interview of forensic cases, highlight the facilitating and attention requiring aspects in the evaluation, and reflect on the perspective of child and adolescent psychiatry. © 2021 Nova Science Publishers, Inc.